THE INFLUENCE OF MACROECONOMIC VARIABLES ON ECONOMIC GROWTH IN INDONESIA - Riza Nabila; Yusrizal Yusrizal; Nur Ahmadi Bi Rahmani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to influence macroeconomic variables on economic growth in Indonesia. Economic growth is seen as a development of economic activity which causes goods and services produced in a country to increase. This research method is quantitative research with secondary data in the 2012-2021 observation period. Secondary data collection uses the documentation method for data on reports of total exchange rates, inflation, interest rates and economic growth from BPS, BPPRP and BPKAP, the data collected is analyzed using multiple linear regression using the eviews 9 computer program. Research results show 1) Value Exchange rate from the results of the multiple linear regression test has a negative and significant effect on economic growth during the 2012-2021 period, meaning that every increase in the exchange rate will reduce economic growth by -1.28%. 2) Inflation has a positive and significant effect on economic growth in 2012-2021, increasing economic growth by 3.83%. 3) The BI-7 Day Reverse Repo Rate (BI7DRR) has no significant effect on economic growth in 2012-2021 and has no impact whatsoever on economic growth. Keywords: Economic Growth, Exchange Rate, Inflation, Interest Rates